Hubungan antara Pemberitaan Vaksin COVID-19 dengan Minat Vaksinasi pada Mahasiswa - Gebriel Rahma Putri; Firmansyah (UNISBA Press, 2022)
Abstract. The Indonesian government announced that the Covid-19 disease was present in the midst of people's lives on March 2, 2020. Starting from this case, the number of people exposed to the Covid-19 disease continued to increase, the government took a policy to organize mass vaccinations. Vaccination activities are carried out as one of the efforts made by the government to create immunity formation specifically for Covid-19 disease and also as an effort to avoid transmission. This study aims to find out the relationship between the news of the Covid-19 vaccine on Kompas.com and the interest in vaccination of Fikom Unisba students. The method used in this study is a quantitative method using correlational analysis techniques. This study uses the Uses and Effect theory proposed by Sven Wandahl which has the aim of knowing the relationship between variables. In this study, using purposive sampling data collection techniques and using the Slovin formula to determine the number of respondents. The results of the hypothesis test are that there is a very strong and unidirectional relationship between the news of the Covid-19 vaccine and the interest in vaccination of students. With a significance of 0.000 <0.05 and a coefficient of 0.712. Abstrak. Pemerintah indonesia mengumumkan bahwa penyakit Covid-19 hadir di tengah kehidupan masyarakat pada 2 Maret 2020. Dimulai dari kasus tersebut, jumlah orang yang terpapar penyakit Covid-19 terus meningkat, pemerintah mengambil kebijakan untuk menyelenggarakan vaksinasi masal. Kegiatan vaksinasi dilaksanakan sebagai salah satu upaya yang dilakukan oleh pemerintah guna untuk menciptakan pembentukan kekebalan tubuh dengan spesifik pada penyakit Covid-19 dan juga sebagai suatu upaya untuk menghindari penularan. Penelitian ini bertujuan untuk mencari tahu hubungan antara pemberitaan vaksin Covid-19 pada Kompas.com dengan minat vaksinasi mahasiswa Fikom Unisba. Metode yang digunakan dalam penelitian ini adalah metode kuantitatif dengan menggunakan teknik analisis korelasional. Penelitian ini menggunakan teori Uses and Effect yang dikemukakan oleh Sven Wandahl yang memiliki tujuan untuk mengetahui hubungan anatar variabel. Dalam penelitian ini menggunakan teknik pengumpulan data purposive sampling dan menggunakan rumus Slovin untuk menentukan jumlah responden. Hasil dari uji hipotesisnya ialah terdapat hubungan yang sangat kuat dan searah antara pemeberitaan vaksin Covid-19 dengan Minat vaksinasi mahasiswa. Dengan signifikansi 0,000<0,05 dan koefisien sebesar 0,712.